A case report on the implantation of a leadless pacemaker in a patient with eosinophilic fasciitis and third-degree atrioventricular block - Li-Juan Huang; Jian-Shu Chen; Qi Zou; Yu-Zhe Song; Yi Yan; Zhao-Fen Wang; Hai-Juan Wang; Peng Chang (BMC Cardiovascular Disorders)
Abstract Eosinophilic fasciitis (EF) is a rare connective tissue disorder characterized by the involvement of the dermis, subcutaneous tissue, and fascia. The treatment for EF usually involves long-term use of glucocorticoids and immunosuppressants. Patients with EF are at risk of developing third-degree atrioventricular (AV) block during the course of the disease. The distinctive features of EF, the side effects of its treatment, and the inherent limitations of transvenous pacemakers (TVPs) present significant challenges in the management of patients with EF who also have third-degree AV block. We present the case of a 64-year-old Chinese male diagnosed with EF and concomitant third-degree AV block. Given the patient’s skin tissue characteristics, the increased risk of infection associated with long-term immunosuppressive therapy, and the potential complications related to TVPs we chose to implant a leadless pacemaker(LP) in the apical region of the right ventricle. This case report underscores the importance of identifying potential cardiovascular complications in EF patients treated with corticosteroids and immunosuppressants. It also highlights the clinical benefit of LP implantation in managing patients with EF and third-degree AV block, especially in terms of minimizing device-related complications and infection risks. This study offers a fresh perspective on the treatment of EF patients who have third-degree AV block and advocates for the use of LPs as a preferred option for cardiac pacing in this patient group. Further research is warranted to evaluate the indications and potential benefits of LPs in a wider range of patients.